Mapping Fluoride Levels in Human Consumption Water in Northeastern Brazil: A Spatial Analysis - , Yann Nobre Viana; , Jader Gabriel Almeida Lima; , Jacques Antonio Cavalcante Maciel; , Myrna Maria Arcanjo Frota Barros; , Mariana Ramalho de Farias; , Celiane Mary Carneiro Tapety; , Ivo Aurélio Lima Júnior; , Yvina Karine Parente Carneiro; , Anastácio Torres de Mesquita Neto; , Nicole França de Vasconcelos (Archives of Current Research International, 2025)
Aims: The present study aimed to assess fluoride concentration levels in water intended for human consumption in the 184 municipalities of the state of Ceará, taking into account geographical variations, in order to identify areas with potential risk of both insufficient exposure, harmful to the prevention of dental caries, and excessive exposure, associated with the development of dental and bone fluorosis. Methodology: The ecological study uses data on fluoride levels in drinking water for the year 2024 in cities in northeastern Brazil. The data was analyzed by calculating the fluoride content per liter, followed by spatial autocorrelation analysis. Results: Fluoride levels below 0.6 mg/L are considered ineffective for preventing dental caries, while concentrations above 0.8 mg/L increase the risk of dental fluorosis, especially in children. The average fluoride level for the state of Ceará was 0.083 mg per liter (ppm). The municipalities of Tianguá and Maracanaú presented the highest fluoride content values, 1 mg/l, 0.89 mg/l, respectively. The municipalities of Carnaubal, Umirim, Boa Viagem and Viçosa do Ceará were the only ones that presented fluoride levels considered ideal, with 0.70 mg/l, 0.72 mg/l, 0.75 mg/l, 0.77 mg/l, respectively. The overall Moran index was 0.483 (p<0.05) in 2024 with the formation of two clusters of municipalities, one of the high-high type, in the northwest portion of the northern part of the state and one of the low-low type, covering the municipalities of the southern region of the state. Conclusion: There is spatial dependence in fluoride levels, with a higher concentration in the northern and northeastern regions of the state, considering the period evaluated, while the municipalities in the southern region, for the most part, have lower values. It is necessary to monitor the fluoridation of public water supplies in Ceará, in order to identify areas with fluoride levels that are not in line with what the Brazilian oral health policy recommends, considering the location of the research, which varies in temperature, something that justifies carrying out spatial analyses.